Poly(A) inclusive RNA isoform sequencing (PAIso−seq) reveals wide-spread non-adenosine residues within RNA poly(A) tails - Yusheng Liu (Nature Portfolio, 2019)
The poly(A) tails on mRNA are vital for their function but it is difficult to map full-length sequences of mRNA isoforms with the entire poly(A) tails. Here the authors develop PAIso−seq which can measure isoform specific poly(A) tail length and base composition at single-cell sensitivity.